Subject Satisfaction with Trifarotene 50 μg/g Cream in the Treatment of Facial and Truncal Acne Vulgaris: A Case Series - Sandra M. Johnson; Rajeev Chavda; Janet C. DuBois (Adis, Springer Healthcare, 2020)
Abstract There is a paucity of literature covering patient-reported outcomes of treatments for truncal acne. Trifarotene 50 μg/g cream is a novel retinoid molecule approved for once-daily topical treatment of facial and truncal acne vulgaris. As physicians are starting to gain real-world experience with this retinoid treatment, their access to reporting from the patient's perspective provides a valuable adjunct to the pivotal studies. We report a case series of three subjects with moderate facial and truncal acne treated with trifarotene 50 μg/g cream on the face, shoulders, upper back and upper anterior chest for 12 weeks and evaluated by satisfaction questionnaires. This case series illustrating the treatment of facial and truncal acne with trifarotene 50 μg/g cream, in the form of real-world data, describes high overall satisfaction and excellent tolerability to support the use of this new retinoid molecule in the treatment of acne vulgaris on both the face and trunk.